The fight for the right to health: Global Capitalism's crisis and accelerated expropriation - Mauricio Torres Tovar (Social Medicine Publication Group, 2014)
During the first week of November 2012, the Uruguayan cities of Piriapolis and Montevideo hosted three - joint - Congresses: the XII Latin Ameri-can Congress of Social Medicine and Collective Health, the XVIII International Congress of Health Policy, and VI Congress of the American Network of Local Health Activists (La Red Américas). This combined event brought together some 700 people from 27 countries. The three sponsoring organizations - the Latin American Social Medicine Association (ALAMES), the International Association of Health Policy (IAHP), and La Red Américas - bring together an important part of the critical health movement known as Social Medicine or Collective Health, a movement that is especially active in Europe and Latin America. The meeting brought together a diverse group, which included academics, researchers, students, health system managers, policy makers, and representatives of social movements. What united these groups was a progressive approach to health based on an analysis that took into account society, politics, culture, and environment.